2019
DOI: 10.1371/journal.pone.0219470
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access and adherence to tuberculosis services, as perceived by patients: A qualitative study in Mozambique

Abstract: Introduction Tuberculosis (TB) continues to be a leading cause of death in Sub-Saharan Africa, including Mozambique. While diagnostic methods and total notifications are improving, significant gaps remain between total numbers of TB cases annually, and the number that are notified. The purpose of this study was to elicit Mozambican patients with drug sensitive TB (DS-TB), TB/HIV and Multi drug resistant tuberculosis (MDR-TB) understanding and assessment of the quality of care for DS-TB, HIV/TB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 20 publications
(21 reference statements)
4
32
0
1
Order By: Relevance
“…TB-related stigma was independently associated with non-submission of sputum, consistent with findings from a study in India [22]. Several studies have reported high perception of TB-associated stigma [23][24][25][26][27], and specific actions are needed to counter this [28,29].…”
Section: Discussionsupporting
confidence: 79%
“…TB-related stigma was independently associated with non-submission of sputum, consistent with findings from a study in India [22]. Several studies have reported high perception of TB-associated stigma [23][24][25][26][27], and specific actions are needed to counter this [28,29].…”
Section: Discussionsupporting
confidence: 79%
“…It appears that the needs of the clinician during the consultation, described as efficiently relaying information on TB treatment and adherence, were met. However, whether this information appropriately addressed the patients concerns and expectations appears only in the context of case-finding in the literature [55][56][57][58][59][60] and not on treatment outcomes in South Africa and globally. Similar findings from a previous study demonstrated that despite standardised guidelines effectively contributing to health coverage; ignoring the subjective biopsychosocial aspects of care particularly in rigid health systems resulted in 'dehumanising' the care process [25].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a gap between the number of people diagnosed with and the number of people notified with TB-this is referred to as pre-treatment lost to follow-up (PTFLU). [10][11][12][13][14] We hypothesized the following situations occurred in the districts where we worked: 1) a number of individuals with TB who present to health facilities are not diagnosed; 2) TB contact tracing could be optimized if Community Health Workers (CHWs) were given a role in it; 3) CHWs could identify individuals that are PTLTFU (people who are tested and have a positive laboratory test for TB, but are not subsequently informed of their results and do not begin treatment for TB) and 4) CHWs can help relink individuals that stop their anti-TB therapy or are lost to follow-up (LTFU) to care. We wanted to evaluate if interventions performed by CHWs to improve all these four weaknesses could lead to an increase in TB notifications at the district level.…”
Section: Introductionmentioning
confidence: 99%